Relationship between economic well-being and e-commerce development - case of China - Cao, Jingyu (2024)
With the rapid development of information technology in recent years, the Internet has gradually integrated into and is dominating people's lives, and e-commerce has become an important business model in our country's market economy system. The development of e-commerce has played an important role in expanding the scale of China's market economy and has also had a significant impact on people's lifestyles, thus studying the influencing factors of e-commerce development is of great value in promoting its sustainable development and improving the efficiency of e-commerce applications. From a practical perspective, as an economic model, the development of e-commerce is inevitably influenced by various macro-environmental factors, especially in recent years, with the impact of the COVID-19 pandemic, offline transactions have been affected in reality, and online transactions have been widely welcomed. At the same time, factors such as per capita GDP, inflation, mobile phone penetration rate, population density, and unemployment rate will also have an impact on the level of e-commerce development. This study attempts to explore the macro-level factors influencing the development of e-commerce, using China as an example to analyze the impact of economic well-being on e-commerce development, with the aim of discussing measures to promote the development of e-commerce from the perspective of macroeconomic factors and providing references for promoting sustainable economic development.